Electrostatic image developing toner, electrostatic image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method

CN114253100BActive Publication Date: 2026-10-23FUJIFILM BUSINESS INNOVATION CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202110252886.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-23
Filing Date
2021-03-08
Publication Date
2026-10-23
Estimated Expiration
2041-03-08

AI Technical Summary

Benefits of technology

[0036]根据上述第1方案,提供一种静电图像显影用色调剂,与含有非晶性聚酯树脂和结晶性聚酯树脂、NCl/NNa小于2.5的静电图像显影用色调剂相比,中间色调图像的定影性优异。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002965531320000371
    Figure BDA0002965531320000371
  • Figure BDA0002965531320000391
    Figure BDA0002965531320000391
  • Figure BDA0002965531320000401
    Figure BDA0002965531320000401
Patent Text Reader

Abstract

The present invention relates to a toner for electrostatic image development, an electrostatic image developer, a toner cartridge, a process cartridge, an image forming apparatus, and an image forming method. The toner for electrostatic image development contains an amorphous polyester resin and a crystalline polyester resin, and satisfies a relationship of 2.5 ≦ N Na and N Cl of a Cl element measured by fluorescent X-ray analysis. Cl ≦ 260.0. Na ​
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a toner for electrostatic image development, an electrostatic image developer, a toner cartridge, a process cartridge, an image forming apparatus, and an image forming method. BACKGROUND

[0002] Japanese Patent Application Publication No. 2012-068307 discloses a toner for electrostatic image development, which has toner particles having residual ammonium ions and silica particles containing a chlorine compound as an external additive.

[0003] Japanese Patent Application Publication No. 2004-287421 discloses a toner for electrostatic image development, in which an electrostatic image developing toner containing a binding resin and a colorant, the binding resin is a polyester resin or a polyol resin, the toner particles contain 0.007 to 0.140 mass% of aluminum and 0.002 to 0.412 mass% of chlorine, the average value of the circularity of the toner particles is 0.94 to 0.99, and the average value of the equivalent circle diameter is 2.6 to 74 μm.

[0004] Japanese Patent Application Publication No. 2019-040024 discloses a toner, which is a toner containing toner particles, the toner particles having a toner core containing a melt-mixed product of an amorphous resin and a crystalline resin, and a shell layer containing a thermosetting resin, wherein the melt-mixed product contains two or more crystalline resin microdomains, and among the two or more crystalline resin microdomains, the proportion of microdomains satisfying the conditions of an axis minor diameter of 50 nm or more and 200 nm or less and an aspect ratio of 4.0 or more and 20.0 or less is 80% or more.

[0005] Japanese Patent Application Publication No. 2017-003990 discloses a toner, which is a toner having toner particles containing an amorphous polyester resin, a crystalline polyester resin, and a wax, wherein there are microdomains of the wax and crystals of the crystalline polyester resin, in a cross-sectional area of the toner, an area occupied by the microdomains of the wax is 0.5% or more and 8.0% or less, an area occupied by the crystals of the crystalline polyester resin is 0.5% or more and 8.0% or less, a number average diameter of the microdomains of the wax is 60 nm or more and 240 nm or less, an aspect ratio of the crystals of the crystalline polyester resin is 5.0 or more and 25.0 or less, and a number average diameter of a long axis length of the crystals of the crystalline polyester resin is 0.8 times or more and 2.0 times or less of the number average diameter of the microdomains of the wax. SUMMARY

[0006] PROBLEMS TO BE SOLVED BY THE INVENTION

[0007] The technical problem to be solved by the present invention is to provide a toner for electrostatic image development, which contains amorphous polyester resin and crystalline polyester resin, and the Net intensity N of Na element determined by fluorescence X-ray analysis. Na The Net intensity N of Cl element determined by fluorescence X-ray analysis Cl 2.5 > N Cl / N Na Compared to toners used in electrostatic image development, midtone images exhibit superior fixing properties.

[0008] According to a first aspect of the present invention, a toner for electrostatic image development is provided, comprising an amorphous polyester resin and a crystalline polyester resin, wherein the Net intensity N of the Na element is determined by fluorescence X-ray analysis. Na The Net intensity N of Cl element determined by fluorescence X-ray analysis Cl Satisfying 2.5≦N Cl / N Na The relationship is ≤260.0.

[0009] According to the second aspect of the present invention, the above-mentioned Net strength N Na With the above Net strength N Cl Satisfying 4.0≦N Cl / N Na The relationship is ≤60.0.

[0010] According to the third aspect of the present invention, the above-mentioned Net strength N Cl The range is between 0.10 kcps and 1.30 kcps.

[0011] According to the fourth aspect of the present invention, the above-mentioned Net strength N Cl The range is between 0.12 kcps and 1.10 kcps.

[0012] According to the fifth aspect of the present invention, the above-mentioned Net strength N Na It is between 0.005 kcps and 0.040 kcps.

[0013] According to the sixth aspect of the present invention, the above-mentioned Net strength N Na It is between 0.010 kcps and 0.030 kcps.

[0014] According to the seventh aspect of the present invention, the crystalline polyester resin comprises a polymer of α,ω-linear aliphatic dicarboxylic acid and α,ω-linear aliphatic diol.

[0015] According to the eighth aspect of the present invention, the polymer of the above-mentioned α,ω-linear aliphatic dicarboxylic acid and α,ω-linear aliphatic diol includes a polymer of 1,10-decanedicarboxylic acid and 1,6-hexanediol.

[0016] According to the ninth aspect of the present invention, the above-mentioned electrostatic image developing toner further contains a release agent, which comprises ester wax.

[0017] According to the 10th aspect of the present invention, the colorant particles have the following characteristics: when the cross-section of the colorant particles is observed, at least two crystalline resin microregions satisfy the following conditions (A), (B1), (C), and (D).

[0018] Condition (A): The aspect ratio of the crystalline resin microregions is 5 or higher and 40 or lower.

[0019] Condition (B1): The major axis length of the crystalline resin microregion is 0.5 μm or more and 1.5 μm or less.

[0020] Condition (C): The angle formed by the extension of the long axis of the crystalline resin micro-region and the tangent (the tangent is the tangent at the junction where the extension meets the surface of the colorant particles) is more than 60 degrees and less than 90 degrees.

[0021] Condition (D): The angle between the extensions of the major axes of the two crystalline resin microregions is more than 45 degrees and less than 90 degrees.

[0022] According to the 11th aspect of the present invention, the colorant particles have the following characteristics: when the cross-section of the colorant particles is observed, at least two crystalline resin microregions satisfy the following conditions (A), (B2), (C), and (D).

[0023] Condition (A): The aspect ratio of the crystalline resin microregions is 5 or higher and 40 or lower.

[0024] Condition (B2): In at least one of the two crystalline resin microregions, the ratio of the major axis length of the crystalline resin microregion to the maximum diameter of the colorant particle is more than 10% and less than 30%.

[0025] Condition (C): The angle formed by the extension of the long axis of the crystalline resin micro-region and the tangent (the tangent is the tangent at the junction where the extension meets the surface of the colorant particles) is more than 60 degrees and less than 90 degrees.

[0026] Condition (D): The angle between the extensions of the major axes of the two crystalline resin microregions is more than 45 degrees and less than 90 degrees.

[0027] According to the 12th aspect of the present invention, the toner particles contain a release agent, and when the cross-section of the toner particles is observed, the micro-regions of the release agent exist inside at a depth of 50 nm or more from the surface of the toner particles.

[0028] According to the 13th aspect of the present invention, the content of the above-mentioned colorant particles is 40% or more relative to all colorant particles.

[0029] According to the 14th aspect of the present invention, the content of the above-mentioned colorant particles is 70% or more relative to all colorant particles.

[0030] According to a 15th aspect of the present invention, an electrostatic image developer is provided, which comprises the above-mentioned electrostatic image developing toner.

[0031] According to the 16th aspect of the present invention, a toner cartridge that is loaded and unloaded in an image forming apparatus is provided, which stores the aforementioned toner for electrostatic image development.

[0032] According to a 17th aspect of the present invention, a processing cartridge that is loaded and unloaded in an image forming apparatus is provided, which includes a developing mechanism that stores the electrostatic image developer and uses the electrostatic image developer to develop an electrostatic image formed on the surface of an image holder into a toner image.

[0033] According to an 18th aspect of the present invention, an image forming apparatus is provided, comprising: an image holder; a charging mechanism for charging the surface of the image holder; an electrostatic image forming mechanism for forming an electrostatic image on the charged surface of the image holder; a developing mechanism for storing the electrostatic image developer and developing the electrostatic image formed on the surface of the image holder into a toner image using the electrostatic image developer; a transfer mechanism for transferring the toner image formed on the surface of the image holder to a surface of a recording medium; and a fixing mechanism for fixing the toner image transferred to the surface of the recording medium.

[0034] According to a 19th aspect of the present invention, an image forming method is provided, comprising the following steps: a charging step, wherein an image holder surface is charged; an electrostatic image forming step, wherein an electrostatic image is formed on the charged image holder surface; a developing step, wherein the electrostatic image formed on the image holder surface is developed into a toner image using the electrostatic image developer; a transfer step, wherein the toner image formed on the image holder surface is transferred to a recording medium surface; and a fixing step, wherein the toner image transferred to the recording medium surface is fixed.

[0035] The effects of the invention

[0036] According to the first embodiment described above, a colorant for electrostatic image development is provided, comprising an amorphous polyester resin and a crystalline polyester resin, N... Cl / N Na Compared to toners used for developing electrostatic images with a value less than 2.5, mid-tone images exhibit superior fixing properties.

[0037] According to the second scheme described above, a colorant for electrostatic image development is provided, which is compatible with N... Cl / N Na Compared to toners used for developing electrostatic images with a color depth less than 4.0, mid-tone images exhibit superior fixing properties.

[0038] According to the third scheme described above, a colorant for electrostatic image development is provided, which is related to the Net intensity N. Cl Compared to toners used for developing electrostatic images with a chromatic concentration of less than 0.10 kcps, midtone images exhibit superior fixing properties.

[0039] According to the fourth scheme described above, a colorant for electrostatic image development is provided, which is related to the Net intensity N. Cl Compared to toners used for developing electrostatic images with a saturation value less than 0.12 kcps, midtone images exhibit superior fixing properties.

[0040] According to the fifth scheme described above, a colorant for electrostatic image development is provided, which is related to the Net intensity N. Na Compared to toners used for developing electrostatic images with a chromatic concentration greater than 0.040 kcps, midtone images exhibit superior fixing properties.

[0041] According to the sixth scheme described above, a colorant for electrostatic image development is provided, which is related to the Net intensity N. Na Compared to toners used for developing electrostatic images with a chromatic concentration greater than 0.030 kcps, midtone images exhibit superior fixing properties.

[0042] According to the above-mentioned 7th or 8th scheme, a toner for electrostatic image development is provided, which has excellent fixing properties for intermediate tone images compared with a crystalline polyester resin that does not include polymers of α,ω-linear aliphatic dicarboxylic acids and α,ω-linear aliphatic diols.

[0043] According to the above-mentioned ninth embodiment, a colorant for electrostatic image development is provided, which provides excellent fixing properties for intermediate tone images compared to release agents that do not contain ester waxes.

[0044] According to the 10th embodiment above, a colorant for electrostatic image development is provided, which has excellent fixing properties for intermediate tone images compared to a colorant for electrostatic image development that does not have colorant particles that satisfy conditions (A), (B1), (C), and (D).

[0045] According to the 11th embodiment above, a colorant for electrostatic image development is provided, which has superior fixing properties for intermediate tone images compared to a colorant for electrostatic image development that does not have colorant particles that satisfy conditions (A), (B2), (C), and (D).

[0046] According to the 12th embodiment above, an electrostatic image developing tone agent is provided, which has excellent fixing properties for intermediate tone images compared to an electrostatic image developing tone agent in which the micro-regions of the release agent exist in the surface layer at a depth of less than 50 nm from the surface of the tone agent particles.

[0047] According to the above-mentioned 13th scheme, a toner for electrostatic image development is provided, which has superior fixing properties for intermediate tone images compared with an electrostatic image development toner in which the content of toner particles satisfying conditions (A), (B1), (C), and (D) is less than 40% of the total toner particles, or compared with an electrostatic image development toner in which the content of toner particles satisfying conditions (A), (B2), (C), and (D) is less than 40% of the total toner particles.

[0048] According to the above-mentioned 14th scheme, a toner for electrostatic image development is provided, which has excellent fixing properties for intermediate tone images compared with an electrostatic image development toner in which the content of toner particles satisfying conditions (A), (B1), (C), and (D) is less than 70% of the total toner particles, or compared with an electrostatic image development toner in which the content of toner particles satisfying conditions (A), (B2), (C), and (D) is less than 70% of the total toner particles.

[0049] According to the 15th embodiment above, an electrostatic image developer is provided, comprising an amorphous polyester resin and a crystalline polyester resin, N... Cl / N Na Compared to electrostatic image developers with a colorant value less than 2.5, mid-tone image fixing properties are superior.

[0050] According to the 16th embodiment above, a colorant cartridge is provided for storing amorphous polyester resin and crystalline polyester resin, N... Cl / N Na Compared to toner cartridges for electrostatic image development with a toner value less than 2.5, the fixing properties of mid-tone images are superior.

[0051] According to the 17th embodiment above, a processing cartridge is provided that exhibits superior fixing properties for intermediate tone images compared to a processing cartridge storing an electrostatic image developer, wherein the electrostatic image developer contains an electrostatic image developing toner, and the electrostatic image developing toner contains an amorphous polyester resin and a crystalline polyester resin, N... Cl / N Na Less than 2.5.

[0052] According to the 18th embodiment described above, an image forming apparatus is provided that exhibits superior fixing properties for intermediate tone images compared to an image forming apparatus that stores an electrostatic image developer in a developing unit. The electrostatic image developer comprises an electrostatic image developing toner containing an amorphous polyester resin and a crystalline polyester resin, N... Cl / N Na Less than 2.5.

[0053] According to the aforementioned 19th embodiment, an image forming method is provided that, compared to an image forming method using an electrostatic image developer in the developing step, exhibits superior fixing properties for intermediate-tone images. This electrostatic image developer comprises an electrostatic image developing toner containing an amorphous polyester resin and a crystalline polyester resin, N... Cl / N Na Less than 2.5. Attached Figure Description

[0054] Figure 1 This is a schematic configuration diagram illustrating an example of the image forming apparatus of this embodiment.

[0055] Figure 2 This is a schematic configuration diagram illustrating an example of a processing cartridge that is mounted and dismounted in an image forming apparatus according to this embodiment.

[0056] Figure 3 This is a schematic diagram showing the cross-section of the toner particles in the electrostatic image developing toner of this embodiment. Detailed Implementation

[0057] The embodiments of the present invention will now be described. These descriptions and examples are for illustrative purposes only and do not limit the scope of the embodiments.

[0058] In this invention, the numerical range represented by “~” indicates the range of values ​​recorded before and after “~” as the minimum and maximum values, respectively.

[0059] In this invention, the upper or lower limit of a numerical range recorded in stages can be replaced with the upper or lower limit of other numerical ranges recorded in different stages. Furthermore, the upper or lower limit of a numerical range recorded in this invention can be replaced with the values ​​shown in the embodiments.

[0060] The term "step" in this invention includes not only independent steps, but also steps that can be clearly distinguished from other steps, as long as the desired purpose of the step can be achieved.

[0061] In this invention, while embodiments are described with reference to the accompanying drawings, the configuration of these embodiments is not limited to the configuration shown in the drawings. Furthermore, the sizes of the components in each figure are schematic, and the relative sizes of the components are not limited thereto.

[0062] Each component in this invention may contain two or more corresponding substances. In this invention, when referring to the amount of each component in a composition, if two or more substances conforming to each component are present in the composition, unless otherwise stated, it refers to the total amount of the two or more substances present in the composition.

[0063] In this invention, the particles conforming to each component may comprise two or more types. When two or more particles conforming to each component are present in the composition, unless otherwise stated, the particle size of each component refers to the value for a mixture of the two or more types of particles present in the composition.

[0064] In this invention, "electrostatic image developing agent" is also simply referred to as "tone agent" and "electrostatic image developing agent" is also simply referred to as "developing agent".

[0065] <Toning agents for electrostatic image development>

[0066] The colorant in this embodiment contains amorphous polyester resin and crystalline polyester resin. The Net intensity (N) of the Na element was determined by fluorescence X-ray analysis. Na The Net intensity N of Cl element determined by fluorescence X-ray analysis Cl Satisfying 2.5≦N Cl / N Na The relationship is ≤260.0.

[0067] In the toning agent of this embodiment, the mid-tone image exhibits excellent fixing properties on the recording medium. The mechanism is presumably as follows.

[0068] Toners may contain sodium (Na) ions. These Na ions may originate from colorants or dispersants used in the wet manufacturing process of toner particles. It is speculated that Na ions form ionic crosslinks with the binding resin on the toner surface, causing the toner surface to harden. Hardened toners tend to have reduced melting points when heated. As a result, the fixing properties of toner images on recording media are reduced, particularly for mid-tone images.

[0069] In contrast, it is speculated that when Cl ions are included in the toner, the Cl ions form a salt with Na ions, thereby inhibiting the formation of ionic crosslinks between Na ions and the adhesive resin, and suppressing the curing of the toner surface. As a result, it can be inferred that images formed with toners containing Cl ions exhibit the expected melting properties when heated, and mid-tone images show excellent fixing properties on the recording medium.

[0070] The net strength N of Cl element Cl Net strength N relative to Na Na The ratio is N Cl / N Na In toning agents with a concentration less than 2.5, the effect of Cl ions relative to Na ions is insufficient, resulting in poor fixing of mid-tone images. From this perspective, N... Cl / N Na The value is 2.5 or higher, preferably 3.0 or higher, and more preferably 4.0 or higher.

[0071] The net strength N of Cl element Cl Net strength N relative to Na Na The ratio is N Cl / N Na In toners with a toning agent value greater than 260.0, secondary transfer defects may occur due to the influence of Cl ions. From this perspective, N... Cl / N Na The value is 260.0 or less, preferably 150.0 or less, and more preferably 60.0 or less.

[0072] Net strength N of Na element Na Net strength N of Cl element Cl The determination method is as follows.

[0073] Approximately 200 mg of toner (including additives if applicable) was compressed using a compression molding machine under a load of 10t for 60 seconds to produce a disc with a diameter of 10 mm and a thickness of 2 mm. This disc was used as a sample for elemental analysis using a scanning fluorescence X-ray analyzer (Rigaku ZSX Primus II) at a tube voltage of 40 kV and a tube current of 70 mA. The net intensities (unit: kilocounts per second, kcps) for Na and Cl were determined.

[0074] The incorporation of Cl ions into the colorant can be achieved, for example, by using chlorides during the manufacture of colorant particles. Ammonium chloride can be cited as an example of a chloride.

[0075] In the toning agent of this embodiment, considering both excellent fixing properties of mid-tone images and suppression of poor secondary transfer, the Net intensity N of the Cl element was measured by fluorescence X-ray analysis. ClPreferably, the concentration is 0.10 kcps or more and 1.30 kcps or less; more preferably, 0.11 kcps or more and 1.20 kcps or less; and even more preferably, 0.12 kcps or more and 1.10 kcps or less.

[0076] In the colorant of this embodiment, the Net intensity N of the Na element, as determined by fluorescence X-ray analysis, is... Na There are no particular limitations, but it is preferably 0.005 kcps or more and 0.040 kcps or less, more preferably 0.007 kcps or more and 0.035 kcps or less, and even more preferably 0.010 kcps or more and 0.030 kcps or less.

[0077] The details of the colorant in this embodiment will be described below.

[0078] The colorant in this embodiment is composed of colorant particles and, if necessary, additives.

[0079] [Toning agent granules]

[0080] Colorant particles may consist of, for example, an adhesive resin and, if necessary, colorants, release agents and other additives.

[0081] -Adhesive resin-

[0082] The adhesive resin includes at least amorphous polyester resin and crystalline polyester resin.

[0083] In this invention, crystalline polyester resin refers to polyester resin that does not exhibit a step-like change in endothermic heat in differential scanning calorimetry (DSC) and has a clear endothermic peak. Specifically, it refers to polyester resin whose endothermic peak half-width is less than 10°C when measured at a heating rate of 10°C / min.

[0084] In this invention, amorphous polyester resin refers to polyester resin whose half-peak width of the endothermic peak is greater than 10°C when measured at a heating rate of 10°C / min, polyester resin exhibiting a step-like change in endothermic heat, or polyester resin for which no definite endothermic peak has been identified.

[0085] Amorphous polyester resin

[0086] Examples of amorphous polyester resins include condensation polymers of polycarboxylic acids and polyols. Commercially available or synthetic amorphous polyester resins can be used.

[0087] Examples of polycarboxylic acids include, for example, aliphatic dicarboxylic acids (such as oxalic acid, malonic acid, maleic acid, fumaric acid, citracic acid, itaconic acid, pentenic acid, succinic acid, alkenyl succinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (such as cyclohexanedicarboxylic acid, etc.), aromatic dicarboxylic acids (such as terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, etc.), their anhydrides, or their lower (e.g., alkyl esters with 1 to 5 carbon atoms). Among these, aromatic dicarboxylic acids are preferred as polycarboxylic acids.

[0088] In polycarboxylic acids, dicarboxylic acids may be used in combination with tricarboxylic acids or more carboxylic acids that have a cross-linked or branched structure. Examples of tricarboxylic acids or more carboxylic acids include trimellitic acid, benzopyrene, their anhydrides, or their lower (e.g., 1 to 5 carbon atoms) alkyl esters.

[0089] Polycarboxylic acids can be used alone or in combination of two or more.

[0090] Examples of polyols include aliphatic diols (such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (such as cyclohexanediol, cyclohexanediol, hydrogenated bisphenol A, etc.), and aromatic diols (such as ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, aromatic diols and alicyclic diols are preferred as polyols, and aromatic diols are more preferred.

[0091] As a polyol, the diol can also be used in combination with a tri- or higher polyol that has a cross-linked or branched structure. Examples of tri- or higher polyols include glycerol, trimethylolpropane, and pentaerythritol.

[0092] Polyols can be used alone or in combination of two or more.

[0093] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 50°C or higher and 80°C or lower, more preferably 50°C or higher and 65°C or lower.

[0094] The glass transition temperature of amorphous polyester resin is determined by the DSC curve obtained by differential scanning calorimetry (DSC), or more specifically, by the "extrapolation of the glass transition onset temperature" as described in the method for determining the glass transition temperature of JIS K7121:1987 "Method for determination of transition temperature of plastics".

[0095] The weight-average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 to 1,000,000, more preferably 7,000 to 500,000. The number-average molecular weight (Mn) of the amorphous polyester resin is preferably 2,000 to 100,000. The molecular weight distribution Mw / Mn of the amorphous polyester resin is preferably 1.5 to 100, more preferably 2 to 60.

[0096] Weight-average molecular weight and number-average molecular weight were determined by gel permeation chromatography (GPC). For the molecular weight determination using GPC, a Tosoh GPC HLC-8120 GPC was used, along with a Tosoh TSKgel SuperHM-M (15 cm) column, and THF solvent was employed. The weight-average and number-average molecular weights were calculated from these results using a molecular weight calibration curve prepared from monodisperse polystyrene standard samples.

[0097] Amorphous polyester resins are obtained by known manufacturing methods. Specifically, for example, they are obtained by: setting the polymerization temperature to 180°C or higher and 230°C or lower, and, as needed, reducing the pressure within the reaction system while removing water or alcohol generated during condensation. If the raw monomers are insoluble or incompatible at the reaction temperature, a high-boiling-point solvent can be added as a dissolving agent to dissolve them. In this case, the condensation reaction is carried out while distilling off the dissolving agent. If monomers with poor compatibility are present in the copolymerization reaction, the monomers with poor compatibility can be pre-condensed with the acid or alcohol to which they are to be condensed, and then polycondensed with the main component.

[0098] As amorphous polyester resins, besides unmodified amorphous polyester resins, modified amorphous polyester resins can also be cited. Modified amorphous polyester resins refer to amorphous polyester resins containing linking groups other than ester bonds, or amorphous polyester resins with resin components different from polyesters bonded by covalent or ionic bonds. Examples of modified amorphous polyester resins include resins whose ends are modified by reacting an amorphous polyester resin with functional groups such as isocyanate groups introduced at the ends with an active hydrogen compound.

[0099] The proportion of amorphous polyester resin in all adhesive resins is preferably 60% by mass or more and 98% by mass, more preferably 65% ​​by mass or more and 95% by mass, and even more preferably 70% by mass or more and 90% by mass.

[0100] Crystalline polyester resin

[0101] Examples of crystalline polyester resins include condensation polymers of polycarboxylic acids and polyols. Commercially available products or synthetic compounds can be used as crystalline polyester resins.

[0102] In order to facilitate the formation of crystalline structures in crystalline polyester resins, condensates obtained from linear aliphatic polymeric monomers are preferred over condensates obtained from polymeric monomers with aromatic rings.

[0103] Examples of polycarboxylic acids include aliphatic dicarboxylic acids (such as oxalic acid, succinic acid, glutaric acid, adipic acid, octanoic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, etc.), their anhydrides, or their lower (e.g., alkyl esters with 1 to 5 carbon atoms).

[0104] In polycarboxylic acids, dicarboxylic acids may also be used in combination with tricarboxylic acids or more that have a cross-linked or branched structure. Examples of tricarboxylic acids include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, or their lower (e.g., alkyl esters with 1 to 5 carbon atoms).

[0105] As polycarboxylic acids, these dicarboxylic acids can be used in combination with dicarboxylic acids having sulfonic acid groups or dicarboxylic acids having olefinic double bonds.

[0106] Polycarboxylic acids can be used alone or in combination of two or more.

[0107] Examples of polyols include aliphatic diols (e.g., straight-chain aliphatic diols with 7 to 20 carbon atoms in the main chain). Examples of aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosenediol. Among these, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferred as aliphatic diols.

[0108] In polyols, diols can also be used in combination with tri- or higher alcohols that have cross-linked or branched structures. Examples of tri- or higher alcohols include glycerol, trimethylolethane, trimethylolpropane, and pentaerythritol.

[0109] Polyols can be used alone or in combination of two or more.

[0110] The content of aliphatic diols in polyols can be 80 mol% or more, preferably 90 mol% or more.

[0111] The melting temperature of the crystalline polyester resin is preferably 50°C to 100°C, more preferably 55°C to 90°C, and even more preferably 60°C to 85°C.

[0112] The melting temperature of crystalline polyester resin is determined by the "melting peak temperature" described in the method for determining the melting temperature of JIS K7121:1987 "Method for determination of the transition temperature of plastics" based on the DSC curve obtained by differential scanning calorimetry (DSC).

[0113] The weight-average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.

[0114] Crystalline polyester resins are obtained, for example, by known manufacturing methods, in the same manner as amorphous polyester resins.

[0115] As a crystalline polyester resin, a polymer of α,ω-linear aliphatic dicarboxylic acid and α,ω-linear aliphatic diol is preferred, considering its ease of forming a crystalline structure and its good compatibility with amorphous polyester resins, which results in improved fixing properties of mid-tone images.

[0116] As an α,ω-linear aliphatic dicarboxylic acid, it is preferable that the alkylene group to which the two carboxyl groups are connected has 3 to 14 carbon atoms. More preferably, the alkylene group has 4 to 12 carbon atoms, and even more preferably, the alkylene group has 6 to 10 carbon atoms.

[0117] Examples of α,ω-linear aliphatic dicarboxylic acids include succinic acid, glutaric acid, adipic acid, 1,6-hexanedicarboxylic acid (commonly known as octanoic acid), 1,7-heptanedicarboxylic acid (commonly known as azelaic acid), 1,8-octanedicarboxylic acid (commonly known as sebacic acid), 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid, with 1,6-hexanedicarboxylic acid, 1,7-heptanedicarboxylic acid, 1,8-octanedicarboxylic acid, 1,9-nonanedicarboxylic acid, and 1,10-decanedicarboxylic acid being preferred.

[0118] α,ω-linear aliphatic dicarboxylic acids can be used alone or in combination with two or more.

[0119] As an α,ω-linear aliphatic diol, it is preferable that the alkylene group to which the two hydroxyl groups are connected has 3 to 14 carbon atoms, more preferably 4 to 12 carbon atoms, and even more preferably 6 to 10 carbon atoms.

[0120] Examples of α,ω-linear aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, and 1,18-octadecanediol, with 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol being preferred.

[0121] α,ω-linear aliphatic diols can be used alone or in combination with two or more.

[0122] As a polymer of α,ω-linear aliphatic dicarboxylic acid and α,ω-linear aliphatic diol, from the perspective of easy formation of crystal structure and good compatibility with amorphous polyester resin, which results in improved fixing of mid-tone images, a polymer selected from at least one of the group consisting of 1,6-hexanedicarboxylic acid, 1,7-heptanedicarboxylic acid, 1,8-octanedicarboxylic acid, 1,9-nonanedicarboxylic acid and 1,10-decanedicarboxylic acid and at least one of the group consisting of 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol and 1,10-decanediol is preferred, with a polymer of 1,10-decanedicarboxylic acid and 1,6-hexanediol being more preferred.

[0123] The proportion of crystalline polyester resin in all adhesive resins is preferably 1% to 20% by mass, more preferably 2% to 15% by mass, and even more preferably 3% to 10% by mass.

[0124] ·Styrene-acrylic resin

[0125] Styrene-acrylic resin can be cited as an example of an adhesive resin. Styrene-acrylic resin is preferably an amorphous resin.

[0126] Examples of styrene monomers constituting styrene-acrylic resins include styrene, α-methylstyrene, methylchlorostyrene, p-chlorostyrene, p-fluorostyrene, p-methoxystyrene, m-tert-butoxystyrene, p-tert-butoxystyrene, p-vinylbenzoic acid, and p-methyl-α-methylstyrene. A single styrene monomer can be used, or two or more monomers can be used in combination.

[0127] Examples of (meth)acrylic monomers constituting styrene-acrylic resins include (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)methacrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentyl (meth)acrylate, isobornyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. A single (meth)acrylic monomer can be used alone, or two or more can be used in combination. In this invention, the term "(meth)acrylic acid" includes both "acrylic acid" and "methacrylic acid".

[0128] The preferred polymerization ratio of styrene monomers to (meth)acrylic monomers, based on mass, is styrene monomers:(meth)acrylic monomers = 70:30 to 95:5.

[0129] Styrene-acrylic resins can also have cross-linked structures. For example, styrene-acrylic resins with cross-linked structures can be manufactured by copolymerizing styrene monomers with (meth)acrylate monomers and cross-linking monomers. There are no particular limitations on the cross-linking monomers, but (meth)acrylate compounds with two or more functional groups are preferred.

[0130] There are no particular restrictions on the production methods of styrene-acrylic resins; for example, solution polymerization, precipitation polymerization, suspension polymerization, bulk polymerization, and emulsion polymerization can be used. Known operations (such as batch, semi-continuous, and continuous processes) can be applied in the polymerization reaction.

[0131] The proportion of styrene-acrylic resin in all adhesive resins is preferably 0% by mass or more and 20% by mass or less, more preferably 1% by mass or more and 15% by mass or less, and even more preferably 2% by mass or more and 10% by mass or less.

[0132] Other adhesive resins

[0133] Other adhesive resins include homopolymers of monomers such as olefinic unsaturated nitrile monomers (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ether monomers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketone monomers (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropyl ketone, etc.), and olefin monomers (e.g., ethylene, propylene, butadiene, etc.), or copolymers composed of two or more of these monomers.

[0134] Other examples of adhesive resins include epoxy resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, modified rosin, and other non-vinyl resins, mixtures of these non-vinyl resins with the aforementioned vinyl resins, or graft polymers obtained by polymerizing vinyl monomers in their coexistence.

[0135] These adhesive resins can be used alone or in combination of two or more.

[0136] The content of the adhesive resin relative to the total amount of colorant particles is preferably 40% to 95% by mass, more preferably 50% to 90% by mass, and even more preferably 60% to 85% by mass.

[0137] -Coloring agents-

[0138] Examples of pigments that can be used as colorants include: carbon black, chrome yellow, Hansa yellow, benzidine yellow, vat yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, sulfur-resistant orange, Voochug red, permanent red, bright carmine 3B, bright carmine 6B, DuPont oil red, pyrazolone red, litho red, rhodamine B lake, lake red C, pigment red, rose red, aniline blue, cyanine blue, oil-soluble blue, methylene chloride, phthalocyanine blue, pigment blue, phthalocyanine green, malachite green oxalate, etc.; acridine-based, xanthine-based, azo-based, benzoquinone-based, azazine-based, anthraquinone-based, thio-indigo-based, dioxazine-based, thiazine-based, azomethyl alkali-based, indigo-based, phthalocyanine-based, aniline black-based, polyacetylenic, triphenylmethane-based, diphenylmethane-based, thiazole-based, etc.

[0139] Colorants can be used alone or in combination of two or more.

[0140] Colorants can be surface-treated as needed, or they can be used in combination with dispersants. Additionally, two or more colorants can be used together.

[0141] The content of the colorant relative to the total amount of colorant particles is preferably 1% to 30% by mass, more preferably 3% to 15% by mass.

[0142] -Release agent-

[0143] Examples of release agents include: hydrocarbon waxes; natural waxes such as carnauba wax, rice bran wax, and candelilla wax; synthetic or mineral / petroleum-based waxes such as lignite wax; ester waxes such as fatty acid esters and lignite esters; and so on. Release agents are not limited to these.

[0144] As a release agent, ester waxes are preferred from the perspective that their good compatibility with amorphous polyester resins can improve the fixing properties of mid-tone images. More preferably, ester waxes formed between higher fatty acids with 10 to 30 carbon atoms and mono- or multi-carbon alcohols with 1 to 30 carbon atoms are preferred.

[0145] Examples of ester waxes include ester compounds formed between a higher fatty acid with 10 or more carbon atoms and an aliphatic alcohol with 8 or more carbon atoms (either mono- or multi-component), and with a melting temperature of 60°C to 110°C (preferably 65°C to 100°C, more preferably 70°C to 95°C).

[0146] Examples of ester waxes include ester compounds formed between higher fatty acids (octanoic acid, capric acid, lauric acid, tetradecanoic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, oleic acid, etc.) and alcohols (methanol, ethanol, propanol, isopropanol, butanol, octanol, lauryl alcohol, myristol, cetyl alcohol, stearyl alcohol, oleyl alcohol, etc. monohydric alcohols; glycerol, ethylene glycol, propylene glycol, sorbitol, pentaerythritol, etc. polyhydric alcohols). Specifically, examples include carnauba wax, rice bran wax, candelilla wax, jojoba oil, wood wax, beeswax, insect wax, lanolin, and lignite ester wax.

[0147] The melting temperature of the release agent is preferably 50°C to 110°C, more preferably 60°C to 100°C.

[0148] The melting temperature of the release agent is determined by the "melting peak temperature" described in the method for determining the melting temperature in JIS K 7121:1987 "Method for determination of the transition temperature of plastics" based on the DSC curve obtained by differential scanning calorimetry (DSC).

[0149] The content of the release agent relative to the total amount of colorant particles is preferably 1% to 20% by mass, more preferably 5% to 15% by mass.

[0150] -Other Additives-

[0151] Other known additives include, for example, magnetic materials, charge control agents, and inorganic powders. These additives are contained in the colorant particles as internal additives.

[0152] -Characteristics of Toning Agent Particles-

[0153] Toner particles can be monolayer toner particles or so-called core / shell toner particles consisting of a core (core particle) and a coating layer (shell) covering the core.

[0154] The core / shell structured colorant particles can, for example, consist of a core and a coating layer, wherein the core is formed by including an adhesive resin and, if necessary, other additives such as colorants and release agents, and the coating layer is formed by including an adhesive resin.

[0155] The volume average particle size (D50v) of the colorant particles is preferably 2 μm or more and 10 μm or less, more preferably 4 μm or more and 8 μm or less.

[0156] Various average particle sizes and particle size distribution parameters of the colorant particles were determined using a Coulter Multisizer II (manufactured by Beckman Coulter) and an ISOTON-II (manufactured by Beckman Coulter) electrolyte.

[0157] During the determination, 0.5 mg to 50 mg of the test sample is added to 2 ml of a 5% aqueous solution of the surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant. This is then added to 100 ml to 150 ml of electrolyte.

[0158] The electrolyte containing the suspended sample was dispersed using an ultrasonic disperser for 1 minute. The particle size distribution of particles ranging from 2 μm to 60 μm was measured using a Coulter Multisizer II with 100 μm pores. 50,000 particles were sampled.

[0159] For the particle size range (interval) divided based on the measured particle size distribution, the cumulative distribution of volume and number is plotted from the small diameter side. The particle size at the cumulative 16% point is defined as the volumetric particle size D16v and the number particle size D16p. The particle size at the cumulative 50% point is defined as the volume average particle size D50v and the cumulative number average particle size D50p. The particle size at the cumulative 84% point is defined as the volumetric particle size D84v and the number particle size D84p.

[0160] Using these values, the volumetric granularity distribution index (GSDv) is expressed as (D84v / D16v). 1 / 2 The number granularity distribution index (GSDp) was calculated to be (D84p / D16p). 1 / 2 Calculated.

[0161] The average roundness of the colorant particles is preferably 0.94 or more and 1.00 or less, more preferably 0.95 or more and 0.98 or less.

[0162] The average roundness of the toner particles is calculated using (equivalent circle circumference) / (circumference) [(circumference of a circle with the same projected area as the particle image) / (circumference of the particle projection image)]. Specifically, it is the value obtained by measuring using the method described below.

[0163] Toner particles, the object of measurement, are attracted and collected to form a flattened flow. A still image of the particles is obtained by momentarily flashing the particle image. The average roundness is calculated using a flow cytometry particle image analyzer (Sysmex FPIA-3000). The number of samples used to calculate the average roundness is 3500.

[0164] When the colorant contains additives, the colorant (developer) to be measured is dispersed in water containing a surfactant, and then subjected to ultrasonic treatment to obtain colorant particles with additives removed.

[0165] The colorant particles are preferably either the first colorant particles or the second colorant particles described below.

[0166] First colorant particles

[0167] When observing the cross-section of the colorant particles, at least two crystalline resin microregions of the colorant particles meet conditions (A), (B1), (C), and (D).

[0168] Condition (A): The aspect ratio of the crystalline resin microregions is 5 or higher and 40 or lower.

[0169] Condition (B1): The major axis length of the crystalline resin microregion is 0.5 μm or more and 1.5 μm or less.

[0170] Condition (C): The angle formed by the extension of the long axis of the crystalline resin micro-region and the tangent (the tangent is the tangent at the junction where the extension meets the surface of the colorant particle) is more than 60 degrees and less than 90 degrees.

[0171] Condition (D): The angle between the extensions of the major axes of the two crystalline resin microregions is more than 45 degrees and less than 90 degrees.

[0172] Second colorant particles

[0173] When observing the cross-section of the colorant particles, at least two crystalline resin microregions of the colorant particles meet conditions (A), (B2), (C), and (D).

[0174] Condition (A): The aspect ratio of the crystalline resin microregions is 5 or higher and 40 or lower.

[0175] Condition (B2): In at least one of the two crystalline resin microregions, the ratio of the major axis length of the crystalline resin microregion to the maximum diameter of the colorant particle is more than 10% and less than 30%.

[0176] Condition (C): The angle formed by the extension of the long axis of the crystalline resin micro-region and the tangent (the tangent is the tangent at the junction where the extension meets the surface of the colorant particle) is more than 60 degrees and less than 90 degrees.

[0177] Condition (D): The angle between the extensions of the major axes of the two crystalline resin microregions is more than 45 degrees and less than 90 degrees.

[0178] The first colorant particles may or may not be the second colorant particles, but are preferably the second colorant particles.

[0179] The second colorant particles may or may not be the first colorant particles, but are preferably also the first colorant particles.

[0180] Figure 3 The diagram schematically shows the cross-section of a colorant particle. Figure 3 The symbols in the text represent: TN: colorant particles, Amo: amorphous resin, Cry: crystalline resin, L Cry : Major axis length of crystalline resin microregions, L T : Maximum diameter of colorant particles, θ A θ is the angle formed by the extension of the major axis of the crystalline resin micro-region and the tangent (the tangent is the tangent at the junction of the extension and the surface of the colorant particle). B The angle between the extensions of the long axes of the two crystalline resin microregions.

[0181] The fixing properties of intermediate-tone images on recording media can be improved by using first-tone or second-tone particles. The reason for this is speculated to be as follows.

[0182] In both the first and second colorant particles, at least two elliptical or needle-shaped crystalline resin microregions with large aspect ratios and long long axes extend from the surface of the colorant particle inwards and are arranged in a crisscross pattern (see reference). Figure 3 It is speculated that during the fixing of toner images containing these toner particles, after heat is applied to the toner particles, heat is easily and rapidly transferred from the surface of the toner particles to their interior through the melting of the elliptical or needle-shaped crystalline resin. It is speculated that, thus, heat is transferred nearly uniformly throughout the toner particles, facilitating melting in a nearly uniform state throughout the toner particles, thereby improving the fixing properties of intermediate-tone images on the recording medium.

[0183] Regarding the first colorant particles, when observing the cross-section of the colorant particles, at least two crystalline resin microregions (preferably at least three crystalline resin microregions) satisfy conditions (A), (B1), (C), and (D).

[0184] From the perspective of fixing the midtone image on the recording medium, the first toner particles are preferably 40% or more, more preferably 70% or more, further preferably 80% or more, and particularly preferably 90% or more, relative to all toner particles. Ideally, the proportion of the first toner particles relative to all toner particles is 100%.

[0185] Regarding the second colorant particles, when observing the cross-section of the colorant particles, at least two crystalline resin microregions (preferably at least three crystalline resin microregions) satisfy conditions (A), (B2), (C), and (D).

[0186] From the perspective of fixing the midtone image on the recording medium, the second toner particles are preferably 40% or more, more preferably 70% or more, further preferably 80% or more, and particularly preferably 90% or more, relative to all toner particles. Ideally, the proportion of the second toner particles relative to all toner particles is 100%.

[0187] Conditions (A), (B1), (B2), (C), and (D) each have a preferred range.

[0188] ·Condition(A)

[0189] From the perspective of fixing of midtone images on the recording medium, the aspect ratio of the crystalline resin micro-regions is 5 to 40, preferably 10 to 40.

[0190] The aspect ratio of a crystalline resin microregion refers to the ratio of its major axis length to its minor axis length (major axis length / minor axis length). The major axis length of a crystalline resin microregion refers to its maximum length. The minor axis length of a crystalline resin microregion refers to the maximum length among the lengths in directions orthogonal to the extension of its major axis length.

[0191] • Condition (B1)

[0192] From the perspective of the fixing properties of midtone images on the recording medium, the long axis length of the crystalline resin microregions (refer to...) Figure 3 L in Cry The size is 0.5μm or more and 1.5μm or less, preferably 0.8μm or more and 1.5μm or less.

[0193] • Condition (B2)

[0194] From the perspective of the fixing properties of midtone images on the recording medium, the long axis length of the crystalline resin microregions ( Figure 3 L in Cry ) relative to the maximum diameter of the colorant particles (Figure 3 L in T The proportion of () is 10% to 30%, preferably 13% to 30%, and more preferably 17% to 30%.

[0195] The maximum diameter of a colorant particle refers to the maximum length of a straight line drawn from any two points on the outline of the cross-section of the colorant particle (the so-called major diameter).

[0196] • Condition (C)

[0197] From the perspective of the fixing properties of intermediate-tone images on the recording medium, the angle formed by the extension of the long axis of the crystalline resin micro-region and the tangent (the tangent being the tangent at the junction where the extension intersects the surface of the toner particle (i.e., the outer edge of the toner particle) is considered. Figure 3 θ A The temperature is between 60 degrees and 90 degrees, preferably between 75 degrees and 90 degrees.

[0198] ·Condition(D)

[0199] From the perspective of the fixing properties of the midtone image on the recording medium, the angle between the intersection of the extensions of the long axes of the two crystalline resin microregions is ( Figure 3 θ B The temperature should be between 45 degrees and 90 degrees, preferably between 60 degrees and 90 degrees.

[0200] • Method for observing the cross-section of colorant particles

[0201] Toner particles (or toner particles with adhering additives) were mixed and embedded in epoxy resin, which was then cured. The cured material was cut using an ultramicrotome (Leica Ultracut UCT) to prepare thin sections with a thickness of 80 nm to 130 nm. The thin sections were stained with ruthenium tetroxide in a desiccator at 30 °C for 3 hours. STEM images of the stained thin sections were then obtained using a high-resolution field emission scanning electron microscope (FE-SEM, Hitachi High-Tech S-4800) in transmission mode (accelerating voltage: 30 kV, magnification: 20,000x). The images included cross-sections of toner particles of various sizes; cross-sections with a particle size greater than 85% of the volume average particle size were selected for observation. Here, the diameter of the toner particle cross-section refers to the maximum length of the straight line drawn from any two points on the outline of the toner particle cross-section (the so-called major axis).

[0202] In the images, amorphous resins, crystalline resins, and release agents are distinguished based on contrast and shape. Using ruthenium staining, amorphous resins (e.g., amorphous polyester resins) show the deepest staining, followed by crystalline resins (e.g., crystalline polyester resins), with release agents showing the lightest staining. By adjusting the contrast, amorphous resins appear black, crystalline resins appear light gray, and release agents appear white.

[0203] Image analysis of the micro-regions of crystalline resin is used to determine whether the toner particles meet conditions (A), (B1), (B2), (C), and (D). After determining the proportion of the first or second toner particles, 100 toner particles are observed, and the ratio of the number of first or second toner particles is calculated.

[0204] From the perspective of the fixing properties of the intermediate tone image on the recording medium, the first tone particles and the second tone particles preferably satisfy the following condition (E).

[0205] • Condition (E): When observing the cross-section of the toner particles, the release agent micro-region exists within a depth of 50 nm or more from the surface of the toner particles. That is, when observing the cross-section of the toner particles, the shortest distance between the release agent micro-region existing in the toner particles and the surface (i.e., the outer edge) of the toner particles is 50 nm or more.

[0206] Condition (E) refers to the release agent micro-regions not being exposed on the surface of the toner particles. Once the release agent micro-regions are exposed on the surface of the toner particles, the additive will preferentially adhere to the exposed portion of the release agent. However, if the release agent micro-regions exist at a depth of more than 50 nm from the surface of the toner particles, the additive will adhere to the surface of the toner particles in a near-uniform manner. As a result, uneven melting of the toner particles during fixing can be suppressed, improving the fixing properties of intermediate-tone images on the recording medium.

[0207] Condition (E) is confirmed by observing the cross-section of the colorant particles as described above.

[0208] From the perspective of the fixing property of the midtone image on the recording medium, the proportion of the first toner particles that satisfy condition (E) relative to all toner particles is preferably 40% or more, more preferably 70% or more, further preferably 80% or more, particularly preferably 90% or more, and ideally 100%.

[0209] From the perspective of the fixing property of the midtone image on the recording medium, the proportion of the second toner particles that satisfy condition (E) relative to all toner particles is preferably 40% or more, more preferably 70% or more, further preferably 80% or more, particularly preferably 90% or more, and ideally 100%.

[0210] [Additives]

[0211] Examples of additives include inorganic particles. Examples of inorganic particles include SiO2, TiO2, Al2O3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, and K2O·(TiO2). n Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, MgSO4, etc.

[0212] The surface of inorganic particles used as additives can be hydrophobically treated. This hydrophobic treatment can be performed, for example, by impregnating the inorganic particles with a hydrophobic agent. There are no particular limitations on the hydrophobic agent; examples include silane-based coupling agents, silicone oils, titanate-based coupling agents, and aluminum-based coupling agents. They can be used alone or in combination. The amount of the hydrophobic agent is typically, for example, between 1 and 10 parts by mass relative to 100 parts by mass of the inorganic particles.

[0213] Other examples of additives include resin particles (such as polystyrene, polymethyl methacrylate, and melamine resin particles) and cleaning and activating agents (such as metal salts of higher fatty acids, such as zinc stearate, and particles of fluorine-based high molecular weight substances).

[0214] The amount of additive added is preferably 0.01% by mass or more and 5% by mass or less, more preferably 0.01% by mass or more and 2.0% by mass or less, relative to the colorant particles.

[0215] [Manufacturing method of colorant]

[0216] The colorant in this embodiment is obtained by adding an additive to the colorant particles after the colorant particles are manufactured.

[0217] Colorant particles can be manufactured using any of the following methods: dry manufacturing (e.g., mixing and pulverizing) or wet manufacturing (e.g., agglomeration and aggregation (agglomeration-1), suspension polymerization, dissolution suspension, etc.). There are no particular limitations on these methods, and well-known methods can be used. Among these, agglomeration and aggregation is preferred for obtaining colorant particles.

[0218] Specifically, in the case of manufacturing colorant particles by agglomeration and merging, the colorant particles are manufactured through the following steps:

[0219] The steps for preparing an amorphous resin particle dispersion containing amorphous resin particles and a crystalline resin particle dispersion containing crystalline resin particles (resin particle dispersion preparation steps).

[0220] The step of agglomerating amorphous resin particles (and other particles if necessary) in an amorphous resin particle dispersion (or in a dispersion after mixing with other particle dispersions as needed) to form first aggregated particles (first aggregated particle forming step).

[0221] The agglomerated particle dispersion containing the first agglomerated particles is mixed with an amorphous resin particle dispersion and a crystalline resin particle dispersion (or the agglomerated particle dispersion containing the first agglomerated particles is mixed with a mixture of an amorphous resin particle dispersion and a crystalline resin particle dispersion), and agglomerated particles are formed by further attaching amorphous resin particles and crystalline resin particles to the surface of the first agglomerated particles. This operation is repeated more than twice to form the second agglomerated particles (the second agglomerated particle formation step).

[0222] The agglomerated particle dispersion containing the second agglomerated particles is mixed with an amorphous resin particle dispersion, and agglomerated in such a way that amorphous resin particles adhere to the surface of the second agglomerated particles to form the third agglomerated particles (the third agglomerated particle formation step); and

[0223] The step of heating the dispersion of agglomerated particles containing the third agglomerated particle to fuse / merge the agglomerated particles and form colorant particles (fusion / merging step).

[0224] The following details each step. The method for obtaining colorant particles containing colorant and release agent is described below; however, colorant and release agent are additives used as needed. Of course, other additives besides colorant and release agent can also be used.

[0225] -Preparation steps for resin particle dispersion-

[0226] Prepare an amorphous resin particle dispersion containing amorphous resin particles and a crystalline resin particle dispersion containing crystalline resin particles.

[0227] Resin particle dispersions are prepared, for example, by dispersing resin particles in a dispersion medium using a surfactant.

[0228] Examples of dispersion media used in resin particle dispersions include aqueous media. Examples of aqueous media include distilled water, ion-exchanged water, and alcohols. These media can be used alone or in combination of two or more.

[0229] Examples of surfactants include: anionic surfactants such as sulfate esters, sulfonates, phosphate esters, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyols. Among these, anionic and cationic surfactants are particularly noteworthy. Nonionic surfactants can also be used in combination with anionic or cationic surfactants. A surfactant can be used alone or in combination with two or more surfactants.

[0230] In resin particle dispersions, common methods for dispersing resin particles in a dispersion medium include using a rotary shear homogenizer, a ball mill with a media, a sand mill, and a bead mill. Depending on the type of resin particles, phase inversion emulsification can also be used to disperse the resin particles in the dispersion medium. Phase inversion emulsification involves dissolving the resin to be dispersed in a hydrophobic organic solvent that can dissolve the resin, adding an alkali to the organic continuous phase (O phase) for neutralization, and then adding an aqueous medium (W phase), thereby inverting the W / O phase to O / W, and dispersing the resin in particulate form in the aqueous medium.

[0231] The volume average particle size of the resin particles dispersed in the resin particle dispersion is preferably 0.01 μm or more and 1 μm or less, more preferably 0.08 μm or more and 0.8 μm or less, and even more preferably 0.1 μm or more and 0.6 μm or less.

[0232] Regarding the volume average particle size of the resin particles, the particle size distribution obtained by means of a laser diffraction particle size distribution measuring device (e.g., the LA-700 manufactured by Horiba Corporation) was used. For the divided particle size range (segment), the cumulative volume distribution was plotted from the smallest particle size side, and the particle size at the cumulative 50% point relative to all particles was measured and taken as the volume average particle size D50v. The volume average particle size of particles in other dispersions was measured in the same way.

[0233] The resin particle dispersion contains preferably 5% by mass or more and 50% by mass or less, more preferably 10% by mass or more and 40% by mass or less.

[0234] Colorant particle dispersions and release agent particle dispersions are prepared in the same manner as resin particle dispersions. That is, the volume average particle size, dispersion medium, dispersion method, and particle content of the particles in the resin particle dispersion are the same for the colorant particles dispersed in the colorant particle dispersion and the release agent particles dispersed in the release agent particle dispersion.

[0235] -Step 1: Formation of Aggregated Particles-

[0236] Amorphous resin particle dispersion, colorant particle dispersion, and release agent particle dispersion are mixed. Then, the amorphous resin particles, colorant particles, and release agent particles are heterogeneously aggregated in the mixed dispersion to form the first aggregated particles, which have a diameter similar to that of the target colorant particles and contain amorphous resin particles, colorant particles, and release agent particles.

[0237] Specifically, for example, a flocculant is added to the mixed dispersion, and the pH of the mixed dispersion is adjusted to acidic (e.g., pH 2 or higher than 5). A dispersion stabilizer is added as needed, and then the mixture is heated to a temperature close to the glass transition temperature of the resin particles (specifically, for example, the glass transition temperature of the resin particles -30°C to -10°C), causing the particles dispersed in the mixed dispersion to agglomerate and form the first agglomerated particles.

[0238] In the first step of forming aggregated particles, for example, a coagulant may be added at room temperature (e.g., 25°C) while the mixed dispersion is stirred using a rotary shear homogenizer, the pH of the mixed dispersion may be adjusted to acidic (e.g., pH 2 or higher than 5), a dispersion stabilizer may be added as needed, and then the mixture may be heated.

[0239] Examples of flocculants include surfactants with polarity opposite to that of the surfactant contained in the mixed dispersion, inorganic metal salts, and metal complexes with a polarity of two or higher. When metal complexes are used as flocculants, the amount of surfactant required is reduced, and the charging characteristics are improved.

[0240] Additives that form complexes or similar bonds with the metal ions of the flocculant can be used as needed. Chelating agents are suitable as such additives.

[0241] Examples of inorganic metal salts include calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide; and so on.

[0242] Water-soluble chelating agents can be used as chelating agents. Examples of chelating agents include hydroxycarboxylic acids such as tartaric acid, citric acid, and gluconic acid; aminocarboxylic acids such as iminodiacetic acid (IDA), nitrotriacetic acid (NTA), and ethylenediaminetetraacetic acid (EDTA); and so on.

[0243] The amount of chelating agent added relative to 100 parts by weight of resin particles is preferably 0.01 parts by weight or more and 5.0 parts by weight or less, more preferably 0.1 parts by weight or more and less than 3.0 parts by weight.

[0244] -Step 2 of Aggregate Particle Formation-

[0245] The dispersion of the first aggregated particles is mixed with a dispersion of amorphous resin particles and a dispersion of crystalline resin particles. Alternatively, the dispersion of the first aggregated particles can be mixed with a mixture of a dispersion of amorphous resin particles and a dispersion of crystalline resin particles. Then, the amorphous resin particles and crystalline resin particles are agglomerated on the surface of the first aggregated particles in the dispersion containing the first aggregated particles, amorphous resin particles, and crystalline resin particles.

[0246] Specifically, for example, in the first aggregated particle formation step, after the first aggregated particles reach the target particle size, an amorphous resin particle dispersion and a crystalline resin particle dispersion are added, and heating is performed below the glass transition temperature of the amorphous resin particles. This agglomeration operation is repeated more than twice to form second aggregated particles.

[0247] In the second agglomerated particle formation step, it is preferable to add a chloride (e.g., ammonium chloride) to the dispersion to mix Cl ions on the surface of the colorant particles.

[0248] -Step 3: Formation of Aggregated Particles-

[0249] The dispersion of agglomerated particles containing the second agglomerated particles is mixed with a dispersion of amorphous resin particles. Then, the amorphous resin particles are agglomerated on the surface of the second agglomerated particles in the dispersion containing the second agglomerated particles and amorphous resin particles.

[0250] Specifically, for example, in the second aggregated particle formation step, after the second aggregated particles reach the target particle size, an amorphous resin particle dispersion is added, and heating is performed below the glass transition temperature of the amorphous resin particles. The pH of the dispersion is then adjusted to stop the aggregation process.

[0251] In the third step of forming aggregated particles, it is preferable to add a chloride (e.g., ammonium chloride) to the dispersion to mix Cl ions on the surface of the colorant particles.

[0252] -Merge / merge steps-

[0253] The dispersion of agglomerated particles containing the third agglomerated particle is heated to, for example, above the glass transition temperature of the amorphous resin particles (e.g., a temperature 10°C to 30°C higher than the glass transition temperature of the amorphous resin particles) to cause the agglomerated particles to fuse / merge, forming colorant particles.

[0254] After heating for fusion / merging, the temperature can be cooled to 30°C at a rate of 5°C / min to 40°C / min. This rapid cooling readily causes shrinkage of the toner particle surface, thus presumably leading to cracking from the interior of the toner particles towards the toner surface.

[0255] Next, the temperature is raised again at a rate of 0.1°C / min to 2°C / min, and maintained at a temperature above the melting temperature of the crystalline resin (-5°C) for at least 10 minutes. Then, the temperature is slowly cooled at a rate of 0.1°C / min to 1°C / min, thereby causing the crystalline resin microdomains to grow along the crack direction. The crystalline resin microdomains grow from the inside of the colorant particles towards the surface, thus satisfying the above conditions.

[0256] Furthermore, for example, when heating to above the melting temperature of the release agent during reheating, the likelihood of release agent micro-regions growing near the surface of the colorant particles increases. Therefore, the heating temperature during reheating is preferably raised to at least 5°C above the melting temperature of the crystalline resin and below the melting temperature of the release agent.

[0257] After the fusion / merging step, the toner particles formed in the solution are subjected to known washing, solid-liquid separation, and drying steps to obtain dried toner particles. Regarding the washing step, from a power efficiency perspective, displacement washing using ion-exchanged water can be fully implemented. Regarding the solid-liquid separation step, from a productivity perspective, methods such as vacuum filtration and pressure filtration can be implemented. Regarding the drying step, from a productivity perspective, methods such as freeze drying, airflow drying, fluidized bed drying, and vibrating fluidized bed drying can be implemented.

[0258] The colorant in this embodiment is manufactured, for example, by adding an additive to and mixing the obtained dried colorant particles. Mixing can be performed using, for example, a V-type mixer, a Henschel mixer, or a Rodier mixer. Furthermore, a vibrating screen, a pneumatic screen, or similar device can be used to remove coarse particles of the colorant as needed.

[0259] <Electrostatic Image Developer>

[0260] The electrostatic image developer of this embodiment contains at least the toner of this embodiment. The electrostatic image developer of this embodiment may be a single-component developer containing only the toner of this embodiment, or it may be a two-component developer formed by mixing the toner with a carrier.

[0261] There are no particular limitations on the carrier, and known carriers can be cited as examples. Examples of carriers include: a coated carrier in which resin is coated onto the surface of a core material formed of magnetic powder; a magnetic powder dispersion carrier in which magnetic powder is dispersed and mixed in a matrix resin; and a resin-impregnated carrier formed by impregnating porous magnetic powder with resin. Magnetic powder dispersion carriers and resin-impregnated carriers can also be carriers in which the constituent particles of the carrier are used as the core material and their surfaces are coated with resin.

[0262] Examples of magnetic powders include: magnetic metals such as iron, nickel, and cobalt; magnetic oxides such as ferrite and magnetite; and so on.

[0263] Examples of resins used for coating and matrix resins include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyethylene ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylate copolymer, pure silicone resins or their modifications comprising organosiloxane bonds, fluoropolymers, polyesters, polycarbonates, phenolic resins, and epoxy resins. Other additives, such as conductive particles, may also be included in the coating and matrix resins. Examples of conductive particles include metals such as gold, silver, and copper, carbon black, titanium dioxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.

[0264] As a method of utilizing the surface of a resin-coated core material, examples include dissolving the coating resin and various additives (used as needed) in a suitable solvent and using the resulting coating layer forming solution. There are no particular limitations on the solvent; it can be selected considering the type of resin used, its coating suitability, etc.

[0265] Specific resin coating methods include: impregnation, in which the core material is impregnated in a coating layer forming solution; spraying, in which the coating layer forming solution is sprayed onto the surface of the core material; fluidized bed method, in which the coating layer forming solution is sprayed while the core material is suspended by flowing air; kneading coating machine method, in which the core material of the carrier is mixed with the coating layer forming solution in a kneading coating machine, and then the solvent is removed; and so on.

[0266] The mixing ratio (mass ratio) of the toner and carrier in the two-component developer is preferably toner:carrier = 1:100 to 30:100, more preferably 3:100 to 20:100.

[0267] <Image forming apparatus, image forming method>

[0268] The image forming apparatus and image forming method of this embodiment will be described.

[0269] The image forming apparatus of this embodiment includes: an image holder; a charging mechanism that charges the surface of the image holder; an electrostatic image forming mechanism that forms an electrostatic image on the charged surface of the image holder; a developing mechanism that stores an electrostatic image developer and develops the electrostatic image formed on the surface of the image holder into a toner image using the electrostatic image developer; a transfer mechanism that transfers the toner image formed on the surface of the image holder to the surface of a recording medium; and a fixing mechanism that fixes the toner image transferred to the surface of the recording medium. Furthermore, the electrostatic image developer of this embodiment is used as the electrostatic image developer.

[0270] An image forming method (the image forming method of this embodiment) is performed using the image forming apparatus of this embodiment. The method includes the following steps: a charging step, in which the surface of an image holder is charged; an electrostatic image forming step, in which an electrostatic image is formed on the charged surface of the image holder; a developing step, in which the electrostatic image formed on the surface of the image holder is developed into a toner image using the electrostatic image developer of this embodiment; a transfer step, in which the toner image formed on the surface of the image holder is transferred to the surface of a recording medium; and a fixing step, in which the toner image transferred to the surface of the recording medium is fixed.

[0271] The image forming apparatus of this embodiment is applicable to the following known image forming apparatuses: a direct transfer method apparatus that directly transfers a toner image formed on the surface of an image holder to a recording medium; an intermediate transfer method apparatus that first transfers a toner image formed on the surface of an image holder to the surface of an intermediate transfer body, and then transfers the toner image transferred to the surface of the intermediate transfer body to the surface of the recording medium a second time; an apparatus equipped with a cleaning mechanism for cleaning the surface of the image holder after the toner image is transferred but before charging; an apparatus equipped with a de-energizing mechanism for irradiating the surface of the image holder with de-energizing light to de-energize it after the toner image is transferred but before charging; and so on.

[0272] In the case where the image forming apparatus of this embodiment is an intermediate transfer method apparatus, the transfer mechanism, for example, uses a configuration having the following components: an intermediate transfer body that transfers a toner image to a surface; a primary transfer mechanism that transfers a toner image formed on the surface of an image holder to the surface of the intermediate transfer body in one step; and a secondary transfer mechanism that transfers the toner image transferred to the surface of the intermediate transfer body to the surface of a recording medium in a second step.

[0273] In the image forming apparatus of this embodiment, the portion including the developing mechanism may, for example, be a cartridge structure (processing cartridge) that is installed and removed from the image forming apparatus. As a processing cartridge, for example, a processing cartridge equipped with a developing mechanism storing the electrostatic image developer of this embodiment is suitable.

[0274] The following shows an example of the image forming apparatus of this embodiment, but it is not limited thereto. In the following description, the main parts shown in the figures will be described, and the description of other parts will be omitted.

[0275] Figure 1 This is a schematic configuration diagram of the image forming apparatus according to this embodiment.

[0276] Figure 1 The image forming apparatus shown includes first to fourth image forming units 10Y, 10M, 10C, and 10K (image forming mechanisms) of an electrophotographic method that outputs images of yellow (Y), magenta (M), cyan (C), and black (K) based on color image data. These image forming units (hereinafter sometimes simply referred to as "units") 10Y, 10M, 10C, and 10K are arranged side-by-side at a predetermined distance from each other in the horizontal direction. These units 10Y, 10M, 10C, and 10K can be processing boxes that are mounted and removed from the image forming apparatus.

[0277] Above each of the units 10Y, 10M, 10C, and 10K, an intermediate transfer belt (an example of an intermediate transfer body) 20 extends through each unit. The intermediate transfer belt 20 is wound around a drive roller 22 and a support roller 24, causing it to rotate in a direction from the first unit 10Y towards the fourth unit 10K. The support roller 24 applies force in a direction separate from the drive roller 22 via springs (not shown), applying tension to the intermediate transfer belt 20 wound around both rollers. An intermediate transfer body cleaning device 30, opposite to the drive roller 22, is provided on the image holding side of the intermediate transfer belt 20.

[0278] The yellow, magenta, cyan, and black toners stored in the toner cartridges 8Y, 8M, 8C, and 8K are supplied to the developing apparatus (an example of a developing mechanism) 4Y, 4M, 4C, and 4K of each unit 10Y, 10M, 10C, and 10K, respectively.

[0279] Units 1 through 4, 10Y, 10M, 10C, and 10K, have the same configuration and operation. Therefore, the first unit 10Y, which forms the yellow image and is located on the upstream side of the intermediate transfer belt in the direction of travel, will be used as an example for explanation.

[0280] Unit 10Y has a photoreceptor 1Y that functions as an image holder. Around the photoreceptor 1Y are arranged in sequence: a charging roller (an example of a charging mechanism) 2Y, which charges the surface of the photoreceptor 1Y to a preset potential; an exposure device (an example of an electrostatic image forming mechanism) 3, which uses a laser line 3Y to expose the charged surface based on a color separation image signal to form an electrostatic image; a developing device (an example of a developing mechanism) 4Y, which supplies the charged toner to the electrostatic image to develop the electrostatic image; a primary transfer roller 5Y (an example of a primary transfer mechanism), which transfers the developed toner image onto an intermediate transfer belt 20; and a photoreceptor cleaning device (an example of a cleaning mechanism) 6Y, which removes the toner remaining on the surface of the photoreceptor 1Y after the primary transfer.

[0281] The primary transfer roller 5Y is positioned inside the intermediate transfer belt 20, opposite to the photosensitive element 1Y. Each unit's primary transfer rollers 5Y, 5M, 5C, and 5K are connected to a bias power supply (not shown) that applies a primary transfer bias voltage. The bias power supply changes the value of the transfer bias voltage applied to each primary transfer roller via a control unit (not shown).

[0282] The following explains the action of forming the yellow image in Unit 1, 10Y.

[0283] First, before the operation, the surface of the photoreceptor 1Y is charged to a potential of -600V to -800V using the charging roller 2Y.

[0284] Photoreceptor 1Y has good electrical conductivity (e.g., a volume resistivity of 1×10⁻⁶ at 20°C). -6 A photosensitive layer is deposited on a substrate (Ωcm or less). This photosensitive layer typically has high resistance (the resistance of common resins), but it has the property that the resistivity of the portion irradiated by the laser line changes when the laser line is irradiated. Therefore, based on yellow image data sent from a control unit (not shown), the laser line 3Y is irradiated by the exposure device 3 onto the surface of the charged photoreceptor 1Y. As a result, an electrostatic image of a yellow image pattern is formed on the surface of the photoreceptor 1Y.

[0285] An electrostatic image is an image formed on the surface of a photoreceptor 1Y by charging. It is a so-called negative latent image, which is formed as follows: the resistivity of the irradiated part of the photosensitive layer is reduced by using a laser line 3Y, causing the charged charge on the surface of the photoreceptor 1Y to flow; on the other hand, the charge remains in the part that is not irradiated by the laser line 3Y, thereby forming the negative latent image.

[0286] The electrostatic image formed on the photoreceptor 1Y rotates to a predetermined developing position as the photoreceptor 1Y rotates. At this developing position, the electrostatic image on the photoreceptor 1Y is developed into a toner image by the developing device 4Y and then visualized.

[0287] The developing apparatus 4Y stores an electrostatic image developer, for example, containing at least a yellow toner and a carrier. The yellow toner, inside the developing apparatus 4Y, becomes triboelectrically charged through agitation, acquiring a charge of the same polarity (negative polarity) as the charge on the photoreceptor 1Y, and is held on a developer roller (an example of a developer holder). The surface of the photoreceptor 1Y then passes through the developing apparatus 4Y, whereby the yellow toner electrostatically adheres to the de-charged latent image portion on the surface of the photoreceptor 1Y, and the latent image is developed using the yellow toner. The photoreceptor 1Y, with the yellow toner image formed, continues to rotate at a preset speed, conveying the developed toner image on the photoreceptor 1Y to a preset primary transfer position.

[0288] When the yellow toner image on the photoreceptor 1Y is transferred to the primary transfer position, a primary transfer bias is applied to the primary transfer roller 5Y. The electrostatic force from the photoreceptor 1Y toward the primary transfer roller 5Y acts on the toner image, transferring the toner image on the photoreceptor 1Y onto the intermediate transfer belt 20. The applied transfer bias at this time has a (+) polarity opposite to the polarity (-) of the toner, and is controlled, for example, to +10 μA in the first unit 10Y by a control unit (not shown).

[0289] On the other hand, the toner remaining on the photoreceptor 1Y is removed and recycled using the photoreceptor cleaning device 6Y.

[0290] The primary transfer bias applied to the primary transfer rollers 5M, 5C, and 5K after 10M in Unit 2 is also controlled according to Unit 1.

[0291] In this way, the intermediate transfer belt 20, which has transferred the yellow toner image using the first unit 10Y, is sequentially transmitted through the second to fourth units 10M, 10C, and 10K, and the toner images of each color are transferred multiple times in an overlay manner.

[0292] The intermediate transfer belt 20, which has undergone multiple transfer of four toner images via units 1 to 4, reaches the secondary transfer section. This secondary transfer section comprises the intermediate transfer belt 20, a support roller 24 in contact with the inner surface of the intermediate transfer belt, and a secondary transfer roller (an example of a secondary transfer mechanism) 26 disposed on the image holding side of the intermediate transfer belt 20. Meanwhile, recording paper (an example of a recording medium) P is fed to the gap between the secondary transfer roller 26 and the intermediate transfer belt 20 at a predetermined time by a supply member, and a secondary transfer bias is applied to the support roller 24. The applied transfer bias has the same polarity (-) as the toner, and the electrostatic force from the intermediate transfer belt 20 toward the recording paper P acts on the toner image, transferring the toner image from the intermediate transfer belt 20 onto the recording paper P. The secondary transfer bias is determined based on the resistance detected by a resistance detection mechanism (not shown) that detects the resistance of the secondary transfer section, and the voltage is controlled accordingly.

[0293] Then, the recording paper P is fed into the pressing part (engaging part) of a pair of fixing rollers in the fixing device (an example of a fixing mechanism) 28, and the toner image is fixed on the recording paper P to form a fixed image.

[0294] Recording paper P used for transferring toner images can include, for example, ordinary paper used in photocopiers and printers using electrophotographic methods. In addition to recording paper P, other examples of recording media include OHP transparent film.

[0295] To further improve the smoothness of the image surface after fixing, it is preferable that the surface of the recording paper P is also smooth. For example, it is suitable to use coated paper, art paper for printing, etc., which are obtained by coating the surface of ordinary paper with resin or the like.

[0296] The recording paper P, which has been fixed with a color image, is sent to the discharge section, thus ending a series of color imaging actions.

[0297] <Processing Box>

[0298] The processing box of this embodiment will be described.

[0299] The processing box of this embodiment is a processing box that is installed and removed from the image forming apparatus. It has a developing mechanism that stores the electrostatic image developer of this embodiment and uses the electrostatic image developer to develop the electrostatic image formed on the surface of the image holder into a toner image.

[0300] The processing box of this embodiment is not limited to the above configuration, and may also be configured to include a developing mechanism and, if necessary, at least one of other mechanisms selected from an image holder, a charging mechanism, an electrostatic image forming mechanism, and a transfer mechanism.

[0301] The following shows an example of the processing box of this embodiment, but it is not limited thereto. In the following description, the main parts shown in the figures will be described, and the description of other parts will be omitted.

[0302] Figure 2 This is a schematic configuration diagram showing the processing box of this embodiment.

[0303] Figure 2 The processing cartridge 200 shown is constructed, for example, by using a housing 117 having a mounting rail 116 and an opening 118 for exposure to integrally combine and hold the photosensitive element 107 (an example of an image holder) with the charging roller 108 (an example of a charging mechanism), the developing device 111 (an example of a developing mechanism), and the photosensitive element cleaning device 113 (an example of a cleaning unit) surrounding the photosensitive element 107, thus forming an ink cartridge.

[0304] Figure 2 In the diagram, 109 represents an exposure device (an example of an electrostatic image forming mechanism), 112 represents a transfer device (an example of a transfer mechanism), 115 represents a fixing device (an example of a fixing mechanism), and 300 represents recording paper (an example of a recording medium).

[0305] Example

[0306] The embodiments of the present invention are described in detail below through examples, but the embodiments of the present invention are not limited to these examples. In the following description, unless otherwise stated, "parts" and "%" are mass measurements.

[0307] <Preparation of Amorphous Polyester Resin Particle Dispersion (A1)>

[0308] ·Terephthalic acid: 70 parts

[0309] Fumaric acid: 30 parts

[0310] Ethylene glycol: 41 parts

[0311] ·1,5-Pentanediol: 48 parts

[0312] The above-mentioned materials were added to a flask equipped with a stirrer, a nitrogen inlet pipe, a temperature sensor, and a distillation column. The temperature was raised to 220°C over a nitrogen flow for 1 hour. One part of tetraethoxytitanium was added relative to 100 parts of the above-mentioned materials. While distilling to remove the generated water, the temperature was raised to 240°C over 0.5 hours. The dehydration condensation reaction was continued at 240°C for 1 hour, and then the reactants were cooled. This yielded an amorphous polyester resin with a weight-average molecular weight of 96,000 and a glass transition temperature of 61°C.

[0313] In a container equipped with a temperature control mechanism and a nitrogen purging mechanism, 40 parts of ethyl acetate and 25 parts of 2-butanol were added to prepare a mixed solvent. Then, 100 parts of amorphous polyester resin were slowly added to dissolve it. A 10% ammonia solution (equivalent to three times the amount of the resin in molar ratio relative to its acid value) was added, and the mixture was stirred for 30 minutes. Next, the container was purged with dry nitrogen, and the temperature was maintained at 40°C. While stirring the mixture, 400 parts of ion-exchanged water were added dropwise to emulsify it. After the addition was complete, the emulsion was returned to 25°C, resulting in a resin particle dispersion containing resin particles with a volume average particle size of 190 nm. Ion-exchanged water was added to this resin particle dispersion to adjust the solid content to 20%, yielding an amorphous polyester resin particle dispersion (A1).

[0314] <Preparation of Crystalline Polyester Resin Particle Dispersion (B1)>

[0315] ·1,10-decanedicarboxylic acid: 265 parts

[0316] ·1,6-Hexanediol: 168 parts

[0317] • Dibutyltin oxide (catalyst): 0.3 parts

[0318] The above material was added to a heated and dried three-necked flask. The air in the flask was replaced with nitrogen to create an inert atmosphere. The mixture was then stirred and refluxed at 180°C for 5 hours with mechanical stirring. Next, the temperature was slowly increased to 230°C under reduced pressure and stirred for 2 hours. Once the viscosity had increased sufficiently, the mixture was air-cooled to stop the reaction. This yielded a crystalline polyester resin with a weight-average molecular weight of 12700 and a melting temperature of 73°C.

[0319] 90 parts of crystalline polyester resin, 1.8 parts of anionic surfactant (TaycaPower, manufactured by TAYCA Corporation), and 210 parts of deionized water were mixed and cooled to 120°C. The mixture was then dispersed using a homogenizer (ULTRA-TURRAXT50, manufactured by IKA Corporation) and further dispersed for 1 hour using a pressure-discharge Gaulin homogenizer to obtain a resin particle dispersion containing resin particles with a volume average particle size of 190 nm. Deionized water was added to this resin particle dispersion to adjust the solid content to 20%, yielding a crystalline polyester resin particle dispersion (B1).

[0320] <Preparation of Styrene Acrylic Resin Particle Dispersion (C1)>

[0321] Styrene: 370 portions

[0322] • n-Butyl acrylate: 30 parts

[0323] Acrylic acid: 2 parts

[0324] • Dodecanethiol: 24 parts

[0325] • Carbon tetrabromide: 4 parts

[0326] The above materials were mixed and dissolved, and the resulting mixture was dispersed and emulsified in a flask in a surfactant solution (a solution obtained by dissolving 6 parts of a nonionic surfactant (Sanyo Chemical Industries, Nonipol 400) and 10 parts of anionic surfactant (TaycaPower, TAYCA Corporation) in 550 parts of ion-exchanged water). Then, while stirring, an aqueous solution obtained by dissolving 4 parts of ammonium persulfate in 50 parts of ion-exchanged water was added to the flask over 20 minutes. Next, after nitrogen purging, the contents of the flask were heated to 70°C in an oil bath while stirring, and maintained at 70°C for 5 hours to continue emulsion polymerization. This yielded a resin particle dispersion containing resin particles with a volume average particle size of 140 nm. Ion-exchanged water was added to this resin particle dispersion to adjust the solid content to 20%, yielding a styrene-acrylic resin particle dispersion (C1).

[0327] <Preparation of Release Agent Particle Dispersion (W1)>

[0328] • Ester wax (manufactured by Nippon Yushi Co., Ltd., WEP-8, melting temperature 79°C): 100 parts

[0329] • Anionic surfactant (manufactured by TaycaPower, TAYCA Corporation): 1 part

[0330] • Ion-exchanged water: 350 parts

[0331] The above materials were mixed and heated to 100°C. After dispersion using a homogenizer (ULTRA-TURRAX T50 manufactured by IKA), the mixture was further dispersed using a pressure-discharge Gaulin homogenizer to obtain a release agent particle dispersion containing release agent particles with a volume average particle size of 220 nm. Ion-exchanged water was added to this release agent particle dispersion to adjust the solid content to 20%, thus preparing release agent particle dispersion (W1).

[0332] <Preparation of Colorant Particle Dispersion (K1)>

[0333] • Carbon black (manufactured by Cabot, Regal 330): 50 parts

[0334] • Anionic surfactant (manufactured by TaycaPower, TAYCA Corporation): 5 parts

[0335] • Ion-exchanged water: 193 samples

[0336] The above materials were mixed and dispersed at 240 MPa for 10 minutes using an Ultimaizer (manufactured by Sugino Machine). Ion-exchanged water was added to obtain a colorant particle dispersion (K1) with a solid content of 20%.

[0337] <Example 1>

[0338] [Preparation of Toning Agent Granules]

[0339] • Ion-exchanged water: 200 parts

[0340] • Amorphous polyester resin particle dispersion (A1): 130 parts

[0341] • Styrene-acrylic resin particle dispersion (C1): 30 parts

[0342] • Release agent particle dispersion (W1): 10 parts

[0343] • Colorant particle dispersion (K1): 15 parts

[0344] • Anionic surfactant (manufactured by TaycaPower, TAYCA Corporation): 2.8 parts

[0345] The above materials were placed in a round stainless steel flask, and 0.1N (0.1mol / L) nitric acid was added to adjust the pH to 3.5. Then, an aqueous solution obtained by dissolving 2.5 parts aluminum sulfate in 30 parts deionized water was added. The mixture was dispersed at 30°C using a homogenizer (ULTRA-TURRAX T50, IKA), and then heated to 45°C in an oil bath, maintaining this temperature until the volume average particle size reached 4.5 μm.

[0346] Next, add 30 parts of amorphous polyester resin particle dispersion (A1) and 15 parts of crystalline polyester resin particle dispersion (B1), and maintain for 30 minutes. Add these two components every 30 minutes, for a total of 4 times.

[0347] Next, add 40 parts of amorphous polyester resin particle dispersion (A1) and 4 parts of ammonium chloride aqueous solution (which is obtained by dissolving 20 parts of ammonium chloride in 80 parts of ion-exchanged water), and adjust the pH to 9.0 using 1N sodium hydroxide aqueous solution.

[0348] Then, while continuing to stir, the temperature was increased to 85°C at a rate of 0.05°C / min. After holding at 85°C for 3 hours, it was cooled to 30°C at a rate of 15°C / min (first cooling). Then, it was heated to 85°C again at a rate of 0.2°C / min (reheating), held for 30 minutes, and then cooled to 30°C at a rate of 0.5°C / min (second cooling).

[0349] The solid components were then filtered out, washed with ion-exchanged water, and dried to obtain colorant particles with a volume average particle size of 5.9 μm (1).

[0350] [Addition of external additives]

[0351] 100 parts of toner particles (1) were mixed with 1.5 parts of hydrophobic silica (manufactured by NIPPON AEROSIL Co., Ltd., RY50) and mixed for 30 seconds at a rotation speed of 10,000 rpm using a sample mill. The mixture was then sieved using a vibrating sieve with a mesh size of 45 μm to obtain toner (1). The volume average particle size of toner (1) was 5.9 μm.

[0352] [Net Strength N] Na and Net strength N Cl [Determination]

[0353] Using the colorant (1) as a sample, a full elemental analysis was performed using an X-ray analysis device (Rigaku ZSX PrimusII) to determine the Net intensities (unit: kcps) of Na and Cl elements.

[0354] [Determination of micro-regions in toner particles]

[0355] The micro-regions in the toner particles were measured according to the method described above. The toner of Example 1 contained toner particles that satisfied all conditions (A), (B1), (B2), (C), (D), and (E), and these toner particles accounted for more than 70% of all toner particles.

[0356] [Making of the carrier]

[0357] 500 parts of spherical magnetite powder (volume average particle size 0.55 μm) were stirred in a Henschel mixer, followed by the addition of 5 parts of a titanate-based coupling agent. The mixture was heated to 100 °C and stirred for 30 minutes. Then, 6.25 parts of phenol, 9.25 parts of 35% formaldehyde, 500 parts of magnetite particles treated with the titanate-based coupling agent, 6.25 parts of 25% ammonia, and 425 parts of water were added to a four-necked flask and stirred while reacting at 85 °C for 120 minutes. The mixture was then cooled to 25 °C, 500 parts of water were added, the supernatant was removed, and the precipitate was washed with water. The washed precipitate was dried under reduced pressure to obtain a support (M) with an average particle size of 35 μm.

[0358] [Mixing of toning agents and carriers]

[0359] The toner (1) and carrier (M) were loaded into a V-type mixer at a mass ratio of toner (1):carrier (M) = 5:95 and stirred for 20 minutes to obtain developer (1).

[0360] <Examples 2-6>

[0361] Increase the amount of ammonium chloride aqueous solution added. In addition, colorant particles (2) to (6) are prepared in the same manner as colorant particles (1).

[0362] Use one of the toner particles (2) to (6) instead of the toner particle (1). Furthermore, the toner particles (2) to (6) and the developer (2) to (6) are made in the same way as the toner particles (1) and the developer (1).

[0363] <Comparative Examples 1-2>

[0364] The amount of ammonium chloride aqueous solution added was increased or decreased. In addition, coloring agent particles (C1) to (C2) were prepared in the same manner as coloring agent particles (1).

[0365] One of the toner particles (C1) to (C2) is used to replace the toner particle (1), and the toner particles (C1) to (C2) and the developer (C1) to (C2) are prepared in the same manner as the toner particles (1) and the developer (1).

[0366] <Example 7>

[0367] [Preparation of Toning Agent Granules]

[0368] • Ion-exchanged water: 200 parts

[0369] • Amorphous polyester resin particle dispersion (A1): 130 parts

[0370] • Crystalline polyester resin particle dispersion (B1): 60 parts

[0371] • Styrene-acrylic resin particle dispersion (C1): 30 parts

[0372] • Release agent particle dispersion (W1): 10 parts

[0373] • Colorant particle dispersion (K1): 15 parts

[0374] • Anionic surfactant (manufactured by TaycaPower, TAYCA Corporation): 2.8 parts

[0375] The above materials were placed in a round stainless steel flask, and the pH was adjusted to 3.5 by adding 0.1N (0.1mol / L) nitric acid. Then, an aqueous solution obtained by dissolving 2.5 parts of aluminum sulfate in 30 parts of deionized water was added. After dispersion at 30°C using a homogenizer (ULTRA-TURRAX T50, IKA), the mixture was heated to 45°C in an oil bath and maintained until the volume average particle size reached 5.0 μm.

[0376] Next, 160 parts of amorphous polyester resin particle dispersion (A1) were added, followed by 20 parts of ammonium chloride aqueous solution (obtained by dissolving 20 parts of ammonium chloride in 80 parts of deionized water). The pH was then adjusted to 9.0 using a 1N sodium hydroxide aqueous solution. The temperature was then increased to 85°C at a rate of 0.05°C / min while stirring, and held at 85°C for 3 hours. After that, the temperature was cooled to 30°C at a rate of 0.5°C / min. The solid components were then filtered out, washed with deionized water, and dried to obtain colorant particles (7) with a volume average particle size of 5.9 μm.

[0377] [Addition of external additives]

[0378] 100 parts of toner particles (7) and 1.5 parts of hydrophobic silica (manufactured by NIPPON AEROSIL Co., Ltd., RY50) were mixed and mixed at a rotation speed of 10,000 rpm for 30 seconds using a sample mill. The mixture was then sieved using a vibrating sieve with a mesh size of 45 μm to obtain toner (7). The volume average particle size of toner (7) was 5.9 μm.

[0379] [Net Strength N] Na and Net strength N Cl [Determination]

[0380] Using the colorant (7) as a sample, a full elemental analysis was performed using an X-ray analysis device (Rigaku Corporation ZSX PrimusII) to determine the Net intensities (unit: kcps) of Na and Cl elements.

[0381] [Determination of micro-regions in toner particles]

[0382] The micro-regions in the colorant particles were measured according to the method described above. The colorant in Example 7 contained neither the first colorant particles nor the second colorant particles.

[0383] [Mixing of toning agents and carriers]

[0384] The toner (7) and carrier (M) were loaded into a V-type mixer at a mass ratio of toner (7):carrier (M) = 5:95 and stirred for 20 minutes to obtain developer (7).

[0385] <Performance Evaluation of Developers>

[0386] [Fixing properties of mid-tone images]

[0387] A modified version of the Fuji Xerox ApeosPortIV C5575 image forming apparatus was prepared, and the developer was stored in the developing unit. After placing the image forming apparatus in an environment of 25°C and 15% relative humidity for one day, 100 mid-tone images with an image density of 5% were output on "P paper" manufactured by Fuji Xerox under the same conditions.

[0388] Weigh the first and 100th images separately. After erasing the midtone images using a Kimwipe (manufactured by NIPPON PAPERCRECIA CO.,LTD), weigh them again. Calculate the weight retention rate (weight after erasure ÷ weight before erasure × 100, unit: %) from the weights before and after erasure. Additionally, visually observe the density difference before and after erasure. Classify the weight retention rate and density difference according to the following criteria.

[0389] G1: The weight retention rate of the 1st and 100th tablets was over 99.5%, and no concentration difference could be confirmed before and after wiping.

[0390] G2: The weight retention rate of the 1st and 100th tablets is over 99.5%, and a very slight concentration difference can be observed before and after wiping.

[0391] G3: The weight retention rate of the 1st and 100th tablets is above 98.0% and less than 99.5%, and the concentration difference can be confirmed before and after wiping.

[0392] G4: The weight retention rate of the 1st and 100th tablets is above 97.0% and below 98.0%, and the concentration difference can be confirmed before and after wiping.

[0393] G5: The weight retention rate of the 1st and 100th tablets is less than 97.0%, and the concentration difference can be confirmed before and after wiping.

[0394] [Transfer efficiency of secondary transfer printing]

[0395] A modified version of the Fuji Xerox ApeosPortIV C5575 image forming apparatus was prepared, and the developer was stored in the developing unit. After placing the image forming apparatus for one day at 30°C and 85% relative humidity, 10,000 images with an image density of 1% were printed on Fuji Xerox P-paper under the same conditions. Next, 3cm x 4cm solid color patches were developed and transferred. The toner image on the intermediate transfer belt was taken using the adhesive properties of the tape surface, and the weight W1 of the transferred toner image was measured. Then, 3cm x 4cm solid color patches were formed on P-paper, and the weight W2 of the image was measured. The transfer efficiency (W2 ÷ ​​W1 × 100, unit: %) was calculated from these weights, and the transfer efficiency was graded according to the following criteria.

[0396] A: The transfer efficiency is over 90%.

[0397] B: Transfer efficiency is above 80% but less than 90%.

[0398] C: Transfer efficiency less than 80%

[0399]

[0400] <Examples 101-129>

[0401] To ensure that the crystalline resin microregions and release agent microregions in the colorant particles possess the characteristics shown in Tables 3 and 4, the type of release agent, the amount of resin particle dispersion used in the second agglomerated particle formation step, the amount of resin particle dispersion used in the third agglomerated particle formation step, and the fusion / merging step were adjusted. Furthermore, colorant particles (101) to (129) were produced in the same manner as colorant particles (1). The cooling rate of the first cooling in the fusion / merging step, the holding temperature after reheating, and the cooling rate of the second cooling were implemented as described in Table 2.

[0402] One of the toner particles (101) to (129) is used instead of the toner particle (1). Furthermore, the toner particles (101) to (129) and the developer (101) to (129) are prepared in the same manner as the toner particles (1) and the developer (1).

[0403] Using colorants (101) to (129) as samples, elemental analysis was performed using an X-ray analysis apparatus (Rigaku ZSX Primus II) to determine the Net intensities (unit: kcps) of Na and Cl. The results showed that in the colorants of Examples 101 to 129, the Net intensity N of Na was... Na Net strength N with Cl element Cl Each satisfies 2.5≦NCl / N Na The relationship is ≤260.0.

[0404] [Table 2]

[0405]

[0406]

[0407] [Table 4]

[0408]

[0409] The symbols in Tables 3 and 4 represent the following items.

[0410] • First colorant particle A: Colorant particle that satisfies conditions (A), (B1), (C), and (D).

[0411] • First colorant particle B: Colorant particles that satisfy conditions (A'), (B1'), (C'), and (D').

[0412] Condition (A'): The aspect ratio of the crystalline resin microregions is 10 or higher and 40 or lower.

[0413] Condition (B1'): The major axis length of the crystalline resin microregion is 0.8 μm or more and 1.5 μm or less.

[0414] Condition (C'): The angle formed by the extension of the long axis of the crystalline resin micro-region and the tangent (the tangent is the tangent at the junction where the extension meets the surface of the colorant particles) is more than 75 degrees and less than 90 degrees.

[0415] Condition (D'): The angle between the extensions of the major axes of the two crystalline resin microregions is more than 60 degrees and less than 90 degrees.

[0416] • Second colorant particle A: Colorant particles that satisfy conditions (A), (B2), (C), and (D).

[0417] • Second colorant particles B: Colorant particles that satisfy conditions (A'), (B2'), (C'), and (D').

[0418] Condition (A'): The aspect ratio of the crystalline resin microregions is 10 or higher and 40 or lower.

[0419] Condition (B2'): The ratio of the major axis length of the crystalline resin microregion to the maximum diameter of the colorant particles is more than 13% and less than 30%.

[0420] Condition (C'): The angle formed by the extension of the long axis of the crystalline resin micro-region and the tangent (the tangent is the tangent at the junction where the extension meets the surface of the colorant particles) is more than 75 degrees and less than 90 degrees.

[0421] Condition (D'): The angle between the extensions of the major axes of the two crystalline resin microregions is more than 60 degrees and less than 90 degrees.

[0422] •AR: Aspect ratio of the micro-regions of crystalline resin.

[0423] ·L Cry : The length of the major axis of the crystalline resin microregion.

[0424] ·θA: The angle formed by the extension of the long axis of the crystalline resin micro-region and the tangent (the tangent is the tangent at the junction where the extension meets the surface of the colorant particles).

[0425] ·θB: The angle between the extensions of the major axes of the two crystalline resin microregions.

[0426] • Shortest distance: The shortest distance between the micro-area of ​​the release agent and the surface (i.e., the outer edge) of the colorant particles.

[0427] ·Ester wax: WEP-5 manufactured by NOF Co., Ltd., melting temperature 85°C.

[0428] • Solid paraffin wax: HNP-0190 manufactured by Nippon Seika Co., Ltd., melting temperature 89℃.

[0429] • Polyethylene wax: Melting temperature 89℃.

Claims

1. A toner for electrostatic image development, comprising an amorphous polyester resin and a crystalline polyester resin. The Net intensity of Na, as determined by fluorescence X-ray analysis. Na The Net intensity N of Cl element determined by fluorescence X-ray analysis Cl Satisfying 2.5≦N Cl / N Na The relationship is ≤260.0, and the above Net strength N Na For values ​​between 0.005 kcps and 0.040 kcps, the net strength N is as follows: Cl For values ​​between 0.10 kcps and 1.30 kcps, The electrostatic image developing toner has the following toner particles: when the cross-section of the toner particles is observed, at least two crystalline resin microregions satisfy the following conditions (A), (B1), (C), and (D). Condition (A): The aspect ratio of the crystalline resin microregions is 5 or higher and 40 or lower. Condition (B1): The major axis length of the crystalline resin microregions is 0.5 μm to 1.5 μm. Condition (C): The angle formed by the extension of the long axis of the crystalline resin micro-region and the tangent described below is between 60 and 90 degrees. This tangent is the tangent at the point where the extension intersects with the surface of the colorant particles. Condition (D): The angle between the extensions of the major axes of the two crystalline resin microregions is more than 45 degrees and less than 90 degrees.

2. A toner for electrostatic image development, comprising an amorphous polyester resin and a crystalline polyester resin. The Net intensity of Na, as determined by fluorescence X-ray analysis. Na The Net intensity N of Cl element determined by fluorescence X-ray analysis Cl Satisfying 2.5≦N Cl / N Na The relationship is ≤260.0, and the above Net strength N Na For values ​​between 0.005 kcps and 0.040 kcps, the net strength N is as follows: Cl For values ​​between 0.10 kcps and 1.30 kcps, The electrostatic image developing toner has the following toner particles: when the cross-section of the toner particles is observed, at least two crystalline resin microregions satisfy the following conditions (A), (B2), (C), and (D). Condition (A): The aspect ratio of the crystalline resin microregions is 5 or higher and 40 or lower. Condition (B2): In at least one of the two crystalline resin microregions, the ratio of the major axis length of the crystalline resin microregion to the maximum diameter of the colorant particle is more than 10% and less than 30%. Condition (C): The angle formed by the extension of the long axis of the crystalline resin micro-region and the tangent described below is between 60 and 90 degrees. This tangent is the tangent at the point where the extension intersects with the surface of the colorant particles. Condition (D): The angle between the extensions of the major axes of the two crystalline resin microregions is more than 45 degrees and less than 90 degrees.

3. The toner for electrostatic image development as described in claim 1 or 2, wherein, The above Net strength N Na With the above Net strength N Cl Satisfying 4.0≦N Cl / N Na The relationship is ≤60.

0.

4. The toner for electrostatic image development as described in claim 1 or 2, wherein, The above Net strength N Cl The range is between 0.12 kcps and 1.10 kcps.

5. The toner for electrostatic image development as described in claim 1 or 2, wherein, The above Net strength N Na It is between 0.010 kcps and 0.030 kcps.

6. The toner for electrostatic image development as described in claim 1 or 2, wherein, The aforementioned crystalline polyester resin comprises polymers of α,ω-linear aliphatic dicarboxylic acids and α,ω-linear aliphatic diols.

7. The toner for electrostatic image development as described in claim 6, wherein, The polymers of the above-mentioned α,ω-linear aliphatic dicarboxylic acids and α,ω-linear aliphatic diols include polymers of 1,10-decanedicarboxylic acid and 1,6-hexanediol.

8. The toner for electrostatic image development as described in claim 1 or 2, wherein, The aforementioned electrostatic image developing toner further contains a release agent, which comprises ester wax.

9. The toner for electrostatic image development as described in claim 1 or 2, wherein, The aforementioned colorant particles contain a release agent. When the cross-section of the aforementioned colorant particles is observed, the micro-regions of the release agent exist within the interior at a depth of more than 50 nm from the surface of the aforementioned colorant particles.

10. The toner for electrostatic image development as described in claim 1 or 2, wherein, The content of the aforementioned colorant particles is more than 40% relative to all colorant particles.

11. The toner for electrostatic image development as described in claim 10, wherein, The content of the aforementioned colorant particles is more than 70% relative to all colorant particles.

12. An electrostatic image developer comprising the toner for electrostatic image development according to any one of claims 1 to 11.

13. A toner cartridge that is loaded and unloaded in an image forming apparatus, wherein the toner for electrostatic image development according to any one of claims 1 to 11 is stored.

14. A processing cartridge that is loaded and unloaded in an image forming apparatus, comprising a developing mechanism that stores the electrostatic image developer of claim 12, and using the electrostatic image developer to develop an electrostatic image formed on the surface of an image holder into a toner image.

15. An image forming apparatus comprising: Image holding volume; A charging mechanism that charges the surface of the image holder; An electrostatic image forming mechanism that forms an electrostatic image on the surface of the charged image holder; A developing mechanism that stores the electrostatic image developer of claim 12 and uses the electrostatic image developer to develop an electrostatic image formed on the surface of the image holder into a toner image. A transfer mechanism that transfers the toner image formed on the surface of the image holder to the surface of the recording medium; as well as A fixing unit fixes the toner image transferred to the surface of the recording medium.

16. An image forming method comprising the following steps: The charging step involves charging the surface of the image holder. The electrostatic image forming step involves forming an electrostatic image on the surface of the charged image holder. The developing step involves developing the electrostatic image formed on the surface of the image holder into a toner image using the electrostatic image developer according to claim 12. The transfer step transfers the toner image formed on the surface of the image holder to the surface of the recording medium; as well as The fixing step involves fixing the toner image transferred to the surface of the recording medium.

Citation Information

Patent Citations

  • Electrostatic charge image developing toner and method for manufacturing same

    JP2004287421A

  • Toner for electrostatic charge image development, electrostatic charge image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method

    JP2012068307A

  • Toner and production method of toner

    JP2017003990A

  • Toner and method for manufacturing the same

    JP2019040024A

  • Electrostatic image-developing toner, electrostatic image developer, toner cartridge, process cartridge, image forming apparatus and image forming method

    CN104345585A